Characteristics of SFS and SF/Polypropylene (SFPP) Composites Reinforced with Aluminum Trioxide as Filler - Arul Murugan M., Rajendran S., Karunakaran M., Sivakumar D., Loganathan D., Sam Prasanna J., Vijay Karan K. (International Journal of Advanced Science and Technology, 2020)
Global energy crisis and environmental pollution have compelled the scientists and engineers to develop alternative materials. The composite materials play a vital role as a substitute for the conventional materials. In particular, composites with natural fibre reinforcement will be environmental friendly. In this work, the locally available Sisal fibre (SF) is identified as a new natural fibre reinforcement. The current research has established the fact that SFs have not been characterized and it have not been utilised as reinforcement in composite materials until today. An attempt has been made to study the characteristics of SFs and SF/polypropylene (SFPP) composites reinforced with Aluminum trioxide as a filler. Fibre-reinforced polymer (FRP) composites are becoming popular materials for reinforcing and strengthening of structure. FRPs have high strength, light weight and excellent resistance to aggressive environments. FRPs materials, as is known, are influenced by environmental conditions such as freezing, thawing, moisture, temperature, solar radiation, and aggressive chemical agents that occur during their service life. The degrading effect of environmental actions on the mechanical properties of FRPs reduces the durability of structures. As a consequence, for an efficient use of FRPs as substitutes, an analysis of the durability of FRP materials considering all possible deteriorating conditions is necessary. One of the most important environmental factors affecting the durability of FRP is the moisture condition. The experimental investigations performed include Tensile, Flexural, impact and hardness tests of Sisal, polypropylene, Aluminium tri hydroxide. The mechanical properties tensile strength and bending strength determined from water exposure are compared with those of the unexposed laminated composites. The mechanical degradation is then analysed and discussed.